2023
DOI: 10.3390/plants12051082
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Radio-Frequency Electromagnetic Field (RF-EMF) on Lettuce (Lactuca sativa)—Evidence for RF-EMF Interference with Plant Stress Responses

Abstract: The increased use of wireless technology causes a significant exposure increase for all living organisms to radio frequency electromagnetic fields (RF-EMF). This comprises bacteria, animals, and also plants. Unfortunately, our understanding of how RF-EMF influences plants and plant physiology remains inadequate. In this study, we examined the effects of RF-EMF radiation on lettuce plants (Lactuca sativa) in both indoor and outdoor environments using the frequency ranges of 1890–1900 MHz (DECT) at 2.4 GHz and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…These three characteristics, internal concentration, rapid heating and low fluid flow, are not integrated into the natural selfprotection of the tissue, which depends on heat transfer by conduction and convection to sunlight and the hot environment. Therefore, the main detrimental consequence on tissues exposed to high frequency EMF would be rapid heating inside the defenseless parts of the tissues, without a proper self-preservation perspective to defend the key functions of the tissues [9,13]. Note that in addition to possibly damaging parts of tissue, excessive and permanent fields can trigger non-thermal effects, that can stimulate nerves, muscles and excitable structures.…”
Section: Tissues Heating Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three characteristics, internal concentration, rapid heating and low fluid flow, are not integrated into the natural selfprotection of the tissue, which depends on heat transfer by conduction and convection to sunlight and the hot environment. Therefore, the main detrimental consequence on tissues exposed to high frequency EMF would be rapid heating inside the defenseless parts of the tissues, without a proper self-preservation perspective to defend the key functions of the tissues [9,13]. Note that in addition to possibly damaging parts of tissue, excessive and permanent fields can trigger non-thermal effects, that can stimulate nerves, muscles and excitable structures.…”
Section: Tissues Heating Adverse Effectsmentioning
confidence: 99%
“…The connections between EMFs and humans in these activities certainly play an important role in human well-being. In addition to these desired dealings, there are undesirable effects on human tissues as well as those of fauna and flora [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These EMF exposures are due to two types of sources, near field (NF) as telephone cells [9], and far field (FF) as antenna towers for telephone cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of mobile communication technology and the popularization of smartphones, electromagnetic exposure due to mobile communications is receiving increasing attention (Balmori, 2022; Jagetia, 2022; Kaur et al., 2023; Tran et al., 2023). Moreover, studies over the years have shown that electromagnetic exposure caused by downlink in mobile communication occupies a significant proportion, so effective measurement of exposure to downlink signals has always been the focus in the field of electromagnetic measurement (Birks et al., 2018; Choi et al., 2018; Eeftens et al., 2018; Koppel et al., 2022; Zhao et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their operating principle, in addition to their functional transmission of waves, they emit parasitic (stray) EMFs. These EMF exposures can interact with objects and living tissues in general [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%